ANALYSIS OF THE EXISTENCE OF GEOTHERMAL MANIFESTATIONS USING FAULT FRACTURE DENSITY (FFD) IN TEMPURAN DISTRICT, MAGELANG REGENCY - Salma khoirunnisa; Wibowo, Nugroho Budi; Rosyida, Hana; Khaerunnisa, Icha; Jannah, Dea Mutiara; Elsha C., Fathunajah; Mery S. A., Indar (KURVATEK, 2024)
Being in an active fire lane means that Indonesia has geothermal potential. The geothermal research location is in the Tempuran area, Magelang Regency. The method used is by using alignment in the National Digital Elevation Model (DEMNas) data and calculating it using the Fault Fracture Density (FFD) method, the result of which is a contour map. This research aims to identify the existence of geothermal manifestations with FFD values. The research results show that the FFD value in the Tempuran geothermal manifestation area varies between 0.09 - 1.80 km/km2. The FFD value shows that the Tempuran geothermal manifestation is in a low density zone. There is no direct correlation between the presence of geothermal manifestations and the FFD value. The Tempuran geothermal manifestation is thought to be related to geological formations composed of volcanic rock and related to an aquifer system, as well as faults that trend northwest-southeast.